The Contribution of Principal's Leadership Style, Teacher Competence, and School Climate Toward Students’ Learning Outcomes - Putri Purnomo Sari; Ganefri Ganefri; Muhammad Anwar (Jurnal Pendidikan Indonesia, 2020)
This study aims to analyze the contribution of principal leadership style, teacher competence, and school climates to the quality of learning outcomes. This study was a quantitative method. Data collection was carried out using a questionnaire and analyzed by multiple linear regression. The results of this study are the relationship between the principal's leadership style and the school climate has t-count 7.15>t-table 1.96; the relationship between teacher competence and school climates has a value of t-count 3.66>t-table 1.96; the relationship between the principal's leadership style and the quality of learning outcomes has t-count 8.13>t-table 1.96; the relationship of teacher competence with the quality of learning outcomes has t-count 5.47>t-table 1.96; the relationship of school climate with the quality of learning outcomes has a t-count value of 5.64>t-table 1.96; the relationship between the principal's leadership style through the school climate with the quality of learning outcomes has a value of t-count 4.43>t-table 1.96; the relationship between teacher competence through school climate and the quality of learning outcomes has t-count 3.07>t-table 1.96.